Global G3 continuity toolpath smoothing for a 5-DoF machining robot with parallel kinematics. (February 2021) - Xie, Zenghui; Xie, Fugui; Liu, Xin-Jun; Wang, Jinsong
Highlights: A global G 3 continuity toolpath smoothing method is proposed for 5-DoF parallel machining robots. Splines are constructed for SLSGs and to guarantee the G 3 continuity between the fitted curves and the adjacent toolpaths. Smoothing for test toolpaths is conducted to show the validity of the proposed method in motion smoothness. Abstract: Toolpath smoothing is an important approach to improve robots' operational stability and machining quality. Nowadays, the corner rounding smoothing and curve fitting smoothing algorithms are usually adopted to process the linear toolpath segments to improve its continuity. But the high order continuity between the fitted curve and its adjacent curves is difficult to be guaranteed. For parallel machining robots (PMRs), the tangential, curvature and curvature derivative discontinuities at the junction may lead to the self-excited vibration of mechanical structure, consequently the machining efficiency and quality are decreased. Under this consideration, a global G 3 continuity toolpath smoothing method for five degrees of freedom (5-DoF) PMRs is proposed. The linear segments toolpath generated by the Computer-Aided Manufacturing (CAM) system is first divided into long linear segments (LLSs) and short linear segments groups (SLSGs) through breakpoint searching. At the junction point, a B-spline transition curve is inserted to blend adjacent toolpaths. For the SLSG, the quintic B-spline is adopted to fit the discrete data points, constraint equations about the derivatives at the start and end points are established to achieve G 3 continuity with the adjacent transition curves. Based on the proposed method, the smoothing for two test toolpaths is carried out, and experiments on a 5-DoF PMR are conducted to show the validity of the method in motion smoothness.